2020
DOI: 10.1175/mwr-d-20-0089.1
|View full text |Cite
|
Sign up to set email alerts
|

Convection Initiation and Growth at the Coast of South China. Part I: Effect of the Marine Boundary Layer Jet

Abstract: Convection initiation (CI) and the subsequent upscale convective growth (UCG) at the coast of South China in a warm-sector heavy rainfall event are shown to be closely linked to a varying marine boundary-layer jet (MBLJ) over the northern South China Sea (NSCS). To elucidate the dynamic and thermodynamic role of the MBLJ in CI and UCG, we conducted and analyzed convection-permitting numerical simulations and observations. Compared to radar observations, the simulations capture CI locations and the following so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 73 publications
6
48
1
Order By: Relevance
“…Even if with the strong southerly component, the wind speeds of BL airflows over the offshore in bad member still is smaller than that in good members, which cause in the negative correlation of the meridional winds at 950 hPa over the offshore with the coastal CI time. These findings differ from numerous studies of the heavy rainfall during the postmonsoon‐onset period of South China (e.g., Du & Chen, 2018, 2019; Du, Chen, Han, Bai, & Li, 2020; Du, Chen, Han, Mai, et al., 2020; Liu et al., 2020), which found the southerly component of the southwesterly BL airflows playing a prominent role on the amount of heavy rainfall over South China after the onset of SCS monsoon. Such difference is consistent with the shift of prevailing marine BL winds over SCS from southeasterly before the monsoon onset to southwesterly after the monsoon onset (M. Li, Luo, Zhang, et al., 2020; Z. Li, Luo, Du, & Chan, 2020).…”
Section: Analyses Of the Sensitivity Experiments And Ensemble Experimentscontrasting
confidence: 99%
See 2 more Smart Citations
“…Even if with the strong southerly component, the wind speeds of BL airflows over the offshore in bad member still is smaller than that in good members, which cause in the negative correlation of the meridional winds at 950 hPa over the offshore with the coastal CI time. These findings differ from numerous studies of the heavy rainfall during the postmonsoon‐onset period of South China (e.g., Du & Chen, 2018, 2019; Du, Chen, Han, Bai, & Li, 2020; Du, Chen, Han, Mai, et al., 2020; Liu et al., 2020), which found the southerly component of the southwesterly BL airflows playing a prominent role on the amount of heavy rainfall over South China after the onset of SCS monsoon. Such difference is consistent with the shift of prevailing marine BL winds over SCS from southeasterly before the monsoon onset to southwesterly after the monsoon onset (M. Li, Luo, Zhang, et al., 2020; Z. Li, Luo, Du, & Chan, 2020).…”
Section: Analyses Of the Sensitivity Experiments And Ensemble Experimentscontrasting
confidence: 99%
“…Numerous studies have revealed various factors contributing to CI in the warm‐sector heavy rainfall events over inland and coastal SC, including terrain effects (Du, Chen, Han, Bai, & Li, 2020; Wang et al., 2014), mesoscale cold pools (Liu et al., 2018; Wu & Luo, 2016), surface heating (Jiang et al., 2017), boundary layer (BL) flows of tropical origins (Luo et al., 2017), land‐sea breeze fronts (X. Chen et al., 2017), low‐level jets (LLJs) (Du & Chen, 2018, 2019), and urban heat island effects interacting with onshore BL airflows (Wu et al., 2019; Yin et al., 2020). Previous studies utilizing integrated observations demonstrated the importance of coastline, coastal terrain, upstream oceanic airflow in the BL, and precipitation‐generated cold outflows/pools in triggering and maintaining the extreme rain‐producing MCSs near the SC coasts (Du, Chen, Han, Mai, et al., 2020; Du, Chen, Han, Bai, & Li, 2020; Liu et al., 2018; Wang et al., 2014; Wu & Luo, 2016). The idealized simulations of X. Chen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the above analysis, it can be found that most coastal EPHR cases have the common characteristics of weather situations in the lower troposphere, that is, there is a BLJ with a center of high wind speed at sea, which is called marine boundary‐layer jet (MBLJ), and the EPHR occurring area is located on the front side of the jet, corresponding to the local convergence area of moisture flux. This is similar to Du (2020)'s research about the effect of MBLJ on CI. That's to say, the boundary layer jet also has an important influence on the occurrence of EPHR, but the specific mechanism is worthy of further study.…”
Section: Synoptic Patterns Related To Ephrsupporting
confidence: 88%
“…As previous studies have suggested, orography can influence the formation of convection thermally by driving warm circulations in the daytime or generating a convergence zone after sunset (Kalthoff et al., 2009; Roe, 2005). It can also trigger convection dynamically by altering boundary‐layer forcing (Cohuet et al., 2011; Thielen & Gadian, 1997; Wilson & Schreiber, 1986), blocking (Wang et al., 2005; Du, Chen, Han, Bai, et al., 2020; Du, Chen, Han, Mai, et al., 2020) or generating mountain waves (de la Torre et al., 2015; Kirshbaum & Durran, 2005), etc. The coexistence of orography and UHI can lead to large variability in low‐level temperature, water vapor, and winds, potentially resulting in substantial modification of local circulations in the atmosphere (Kim & Baik, 2005; Lin et al., 2011; Rozoff et al., 2003).…”
Section: Introductionmentioning
confidence: 99%